2018
DOI: 10.14419/ijet.v7i3.14.16882
|View full text |Cite
|
Sign up to set email alerts
|

Watershed Sustainability Index for Langat UNESCO HELP River Basin, Malaysia

Abstract: The study on Watershed Sustainability Index (WSI) has been conducted to analyst the environmental condition in the area incorporating ecological baseline and socio-economic conditions. WSI is an integrated indicator based on basin Hydrology, Environment, Life and Policy (HELP) state condition. It is suitable to be applied in the Langat River Basin in Malaysia which has similar catchment area (up to 2,350 km2) and is one of the UNESCO HELP River Basin since 2004. The WSI analysis which uses a pressure–state–res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Furthermore, it was found that to facilitate the development of integrated and holistic strategies for addressing water-related challenges and advancing the goals of sustainable development, in 44% of the publications, variables from all domains, i.e., social, economic, environmental, institutional, and built/infrastructure, were applied. Examples of indices that apply to all domain indicators include the watershed sustainability index [37], water sustainability index [38], West Java water sustainability index (WJWSI) [39,40], and river basin water sustainability index (RBWSI) [15]. It is apparent that these tools recognize the interconnectedness of sustainability.…”
Section: Domains For Holistic Sustainable Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was found that to facilitate the development of integrated and holistic strategies for addressing water-related challenges and advancing the goals of sustainable development, in 44% of the publications, variables from all domains, i.e., social, economic, environmental, institutional, and built/infrastructure, were applied. Examples of indices that apply to all domain indicators include the watershed sustainability index [37], water sustainability index [38], West Java water sustainability index (WJWSI) [39,40], and river basin water sustainability index (RBWSI) [15]. It is apparent that these tools recognize the interconnectedness of sustainability.…”
Section: Domains For Holistic Sustainable Developmentmentioning
confidence: 99%
“…In the case of the watershed sustainability index (WSI), we also found that different studies showcased variations in methodology and understanding. Elfithri et al (2018) focused on the Langat River Basin in Malaysia, employing the WSI to analyze the environmental and socio-economic conditions based on the UNESCO-HELP state condition indicators [37]. Mititelu-Ionuş (2017) conducted research in the Motru River basin in Romania, developing a WSI using indicators such as water availability, water quality, land use, and education [63].…”
Section: Six Clusters Of Water Sustainability Indicesmentioning
confidence: 99%